‘Urban Christianity’ in the United States After World War II - Wild, Mark (History compass, 2011)
This article examines recent scholarship on Christian leaders, churches, and organizations in Post-World War II Urban America. Despite the fact that the vast majority of Americans live in urban areas and that about three quarters of Americans still identify as Christian, a widespread belief that cities foster secularization has obscured the role played by urban Christianity in modern American history. In the last 15 years, numerous historians have challenged this secularization thesis by detailing the ways in which Christians attempted to build and maintain their communities within a changing metropolitan landscape after 1945. Their work makes a compelling argument for the relevance of Christianity to modern American urban history. Future scholarship on urban Christianity should build on this historiography, particularly by addressing the growth of non-denominational and evangelical churches in U.S. cities as well as the theological dimensions of Christian community-formation and activism.